2015
DOI: 10.1002/2014wr015331
|View full text |Cite
|
Sign up to set email alerts
|

Transverse mixing in three-dimensional nonstationary anisotropic heterogeneous porous media

Abstract: Groundwater plumes originating from continuously emitting sources are typically controlled by transverse mixing between the plume and reactants in the ambient solution. In two-dimensional domains, heterogeneity causes only weak enhancement of transverse mixing in steady-state flows. In threedimensional domains, more complex flow patterns are possible because streamlines can twist. In particular, spatially varying orientation of anisotropy can cause steady-state groundwater whirls. We analyze steadystate solute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
86
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 88 publications
(134 reference statements)
2
86
1
Order By: Relevance
“…Several notable studies, however, have shown that transverse dispersion can not be neglected as it plays a key role in the dilution and mixing of solutes and mixing-limited reactive transport [14,13,31,15,7,8,16,20]. The main goal of our study is to devise an experimental technique capable of quantifying three-dimensional 10 transverse dispersion and dilution in natural porous media by providing several quantities such as the transverse dispersion coefficient [41], the dilution index, and the reactor ratio [29].…”
Section: Introductionmentioning
confidence: 99%
“…Several notable studies, however, have shown that transverse dispersion can not be neglected as it plays a key role in the dilution and mixing of solutes and mixing-limited reactive transport [14,13,31,15,7,8,16,20]. The main goal of our study is to devise an experimental technique capable of quantifying three-dimensional 10 transverse dispersion and dilution in natural porous media by providing several quantities such as the transverse dispersion coefficient [41], the dilution index, and the reactor ratio [29].…”
Section: Introductionmentioning
confidence: 99%
“…Kitanidis, 1994;Mattle et al, 2001;Mays and Neupauer, 2012;Cirpka et al, 2015). Subsurface flow mixing is generally decomposed into an advective transport process combined with diffusion/dispersion (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Janković et al (2009) coined the phrase advective mixing to describe these phenomena. Cirpka et al (2015) identified three advective mixing phenomena that enhance solute mixing: (i) streamline focusing/defocusing, (ii) depth-dependent streamline meandering (i.e. streamline deviation), and (iii) secondary motion consisting in persistent twisting, folding, and intertwining of streamlines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sposito [26], and more recently Chiogna et al [27], studied vorticity in both locally isotropic and anisotropic conductivity fields. Several studies [28,29] showed how non-uniformity in the statistical properties of the hydraulic conductivity field can lead to spiralling flows, which affect solute mixing rates. Similar kinematics analysis was conducted by Raats [30].…”
Section: Introductionmentioning
confidence: 99%